Pendidikan Karakter dalam Pembelajaran pada Mahasiswa Calon Guru Matematika - Yudi Darma; Utin Desy Susiaty; Dona Fitriawan (Universitas Indraprasta PGRI Jakarta, 2018)
The aim of the research is to study: 1) how prospective mathematics teachers plan character education in learning; 2) how prospective mathematics teachers carry out character education in learning; 3) how prospective mathematics teachers assess character education in learning. The research is a qualitative descriptive research. The research subjects are IKIP PGRI Pontianak teachers, especially those in Mathematics Education study program. Based on the results of the research, it can be concluded that. 1) Prospective mathematics teachers plan well the character education, internalize it in the KKNI curriculum and design it according to the indicators set in the SNP-PT guidelines. 2) Prospective mathematics teachers carry out well the character education. 3) Prospective mathematics teachers assess very well the character education as an improvement in character in the study program environment